Post-collisional magmatism associated with the final closure of the Rushan-Pshart Meso-Tethys Ocean in Pamir, Tajikistan: Inference from Cretaceous igneous rocks of the Pshart accretionary complex - Yogibekov, Dzhovid; Sang, Miao; Xiao, Wenjiao; Mamadjonov, Yunus; Zhou, Chuanming; Yang, He; Mao, Qigui; Aminov, Jovid; Khalimov, Gufron; Ashuraliev, Sohibnazar (Frontiers in Earth Science, 2023)
The Pamir orogen was formed by the subducted accretion and amalgamation of Cimmerian terranes from the northern margin of Gondwana with the southern margin of Eurasia. The Mesozoic magmatic rocks are widespread in Pamir and record the tectonic evolution in different stages. The Rushan–Pshart suture zone represents an ancient ocean between Central and Southern Pamir. This paper reports the petrography, geochronology, and geochemistry of Cretaceous granites and diabase dikes that intrude into the Pshart complex. The granites were emplaced between 124 and 118 Ma, based on their zircon U-Pb ages. These granites are characterized by high-K calc-alkaline, low magnesian, and high SiO2, A/CNK, and K2O+Na2O values. They also display strong depletion of Ba, Sr, Eu, and Ti and comparatively weak negative Nb anomalies in spidergrams. Thus, we proposed in this study that these are highly fractionated, strongly peraluminous S-type granites. They were generated by the partial melting of the metasedimentary rocks in the plagioclase stability field and underwent subsequent fractional crystallization during their ascent. The diabase dikes contain low SiO2, and high MgO levels and negative Nb and Ta anomalies, which were interpreted to form in an extensional environment. Late Jurassic–Early Cretaceous closure of the Rushan–Pshart Ocean and subsequent foundering of its oceanic lithosphere caused local extension and upwelling of the asthenospheric mantle. The underplating of mafic magma provided a heat source to melt the metasedimentary-derived granitic that formed in the initial post-collisional environment. The subsequent local extension caused the emplacement of diabase dikes. Based on our new data and combined with data from previous studies, we concluded that the Rushan–Pshart suture zone is the remnant of the Meso-Tethys Ocean and may represent the western continuation of the Bangong–Nujiang suture of the Tibetan Plateau.